Household spending : who spends how much on what (Money Series., 2012)
Based on data collected by the Bureau of Labor Statistics' 2011 Consumer Expenditure Survey, this report examines how much American households spend on hundreds of products and services, all organized by demographics. It discusses who is buying what, and how much they spend. Also included in this edition is a comparison of spending trends before and after the Great Recession.